2022
DOI: 10.7241/ourd.2022e.44
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of palmoplantar keratoderma: development and analysis methods

Abstract: Palmoplantar keratoderma (KPP) is a group of inherited or acquired conditions characterized by palmar and plantar hyperkeratosis. The analysis can be difficult, however, thanks to dermoscopy, which is a non-invasive means of exploration, certain signs are very orienting for the right diagnosis. The available data concerning the dermoscopic profile of palmoplanar pathologies are still limited in the literature. we have reviewed the dermoscopic signs of KPP which target the acquired inflammatory dermatoses frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…In the current study, diffuse white scaling was the most prominent feature of psoriasis; it was observed in 83% of cases, which is almost identical to the findings of the studies by Adabala et al [ 10 ] and Çetinarslan et al [ 11 ], where predominantly diffuse scaling was observed in 76.3% (29/38) and 74.3% (26/35) of cases, respectively. Similar findings were also reported in the study conducted by Dassouli et al [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, diffuse white scaling was the most prominent feature of psoriasis; it was observed in 83% of cases, which is almost identical to the findings of the studies by Adabala et al [ 10 ] and Çetinarslan et al [ 11 ], where predominantly diffuse scaling was observed in 76.3% (29/38) and 74.3% (26/35) of cases, respectively. Similar findings were also reported in the study conducted by Dassouli et al [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ability to assess keratinization in the acral areas using this scale has several clinical implications. Firstly, it can aid in the early detection and differentiation of various dermatological conditions that involve hyperkeratosis, such as palmoplantar keratoderma or psoriasis [40,41]. Its importance will be particularly pronounced in the evaluation of plantar hyperkeratotic patterns in older patients, as hyperkeratotic alterations in this demographic can result in gait disturbances, reduced quality of life, and pose potential risks, particularly among individuals with diabetes [15,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The association between PPK and ocular findings has to lead to Hanhart Richner's disease [2]. This is a rare autosomal recessive disorder caused by a deficiency of tyrosine aminotransferase [3]. Clinical presentation of PPK is often focal in two major patterns: nummular type with oval and keratotic plaques mainly over pressure points; the striate type with linear hyperkeratotic lesions extending mostly from the palms to the volar surface of fingers.…”
mentioning
confidence: 99%